Corruption and cleptocracia - Lamas Puccio, Luis (2020)
Making a synthesized introduction to the problem of corruption and its relations with kleptocracy, in an increasingly interrelated and globalized world, in which the digitization of interpersonal relationships prevails, implies in several senses trying to summarize or rather articulate, in a single literary text a great variety of indistinct and conflicting difficulties, related to a particularly topical and current problem.